Estudo fitoquímico e antimicrobiano das raízes de Maytenus distichophylla Mart. ex Reissek (Celastraceae) guiado por GNPS/espectrometria de massas - Figueiredo, Pedro Thiago Ramalho de (2022)
Maytenus is considered the most representative genus of the Celastraceae family, being represented by approximately 123 species distributed in tropical and subtropical regions of the world. In Brazil, Maytenus species show good adaptation to the local climate, and the country is considered the region with the greatest diversity of described species of the genus. 49 species were reported, 36 of which are considered endemic to Brazilian regions. This genus has great relevance for the treatment of gastrointestinal disorders, as well as for infectious and inflammatory processes. Maytenus distichophylla Mart. ex Reissek is popularly known as “pau-colher”, “casca-amarela”, “pau-doce” is endemic to the Northeast region of Brazil, being used in folk medicine to treat chronic kidney disease and stomach ulcers. The pyridine sesquiterpene alkaloids considered chemotaxonomic markers in this genus are found in Maytenus roots. The objective of this work was to carry out a phytochemical and chemoinformatic study of M. distichophylla and to evaluate the antimicrobial activity of extracts and isolated substances. The roots of M. distichophylla were collected in the municipality of Matureia-PB. Subsequently, the roots were dried and crushed to obtain the vegetable powder, which was subjected to successive extractions with 95% ethanol to obtain the crude ethanolic extract (CEE), being subjected to chromatographic methods for isolation and purification of secondary metabolites. In addition to having obtained the molecular network to evaluate the profile of secondary metabolites present in this extract. The chemical identification of the isolated substances was performed by the 1H, 13C and two-dimensional Nuclear Magnetic Resonance spectroscopic method. The molecular network reported the presence of 233 nodes and 17 clusters, in which four clusters were studied. In these, the presence of flavanols, glycosylated flavonoids, condensed tannins and sesquiterpene pyridine alkaloids were putatively noted. Six sesquiterpene pyridine alkaloids (SPA) were isolated from the hexane:acetate (8:2) phases (Ebinifoline E2) and from the dichloromethane phase (Ebinifoline W1, Euojaponine K, F, A and Maiteine), being reported for the first time in this species. Computational studies were carried out to evaluate the prediction of these compounds in models against the microorganisms C. albicans, C. tropicalis, C. parapsilosis, P. aeruginosa and S. epidermides. The Random Forest prediction model for the mentioned microorganisms obtained a percentage of accuracy above 70%, area under the curve, Receiver Operating Characteristic, above 0.82. From this study, the six ASPs were predicted to be active against the microorganisms C. albicans, C. tropicalis, C. parapsilopsis with potential activity ranging from 54% to 79%. Then, the antimicrobial activity of the phases and isolated substances was performed using the bacterial strains: S. aureus ATCC-25923, S. epidermidis ATCC-12228, E. coli ATCC-1873, P. aeruginosa ATCC-9027, C. parapsilosis ATCC-22019, C. albicans ATCC-90028, C. albicans LM-22, in which the extracts and substances tested showed activities for Gram-positive bacteria and yeast fungi. Therefore, this work contributed to the chemical and pharmacological knowledge of M. distichophylla, corroborating the presence of ASP in the roots of this species, in addition to proving the antifungal potential of ASP.